PENERAPAN MODEL AISAS PADA MARKETING DIGITAL LEMBAGA AMIL ZAKAT DALAM MENINGKATKAN KEPERCAYAAN MASYARAKAT - Mokhammad Fazar; Ali Hamdan (Program Studi Ekonomi Syariah, STAI AN-NAJAH INDONESIA MANDIRI, 2024)
In today's era of globalization, rapid technological advances have driven progress in many social areas. Today's technological advances are triggering a shift in marketing strategies towards more contemporary ones.This study aims to test and find out how the application of the AISAS model in the digital marketing of the Amil Zakat Institute in increasing public trust and the strategy of LAZNAS Yatim Mandiri in increasing public trust through digital marketing. The method used in this study is a qualitative descriptive method that relies on the AISAS model (Attention, Interest, Search, Action, &; Share). Data collection techniques in this study are interviews, observation, documentation, and library data collection. The results of this study show that (1) LAZNAS Yatim Mandiri uses a promotion system in the form of share to share activities or programs of institutions that have been run. The biggest platforms are websites, youtube, instagram, and tiktok. (2) The success of LAZNAS Yatim Mandiri in implementing its excellent programs in the midst of very tight competition between Zakat Institutions. This success is due to the implementation of a consistent and well-integrated digital marketing strategy and in line with the AISAS Model strategy, namely: Attention, Interest, Search, Action, and Share. Keywords : Efficiency, Marketing, AISAS, Trust Model, Community Daftar Pustaka Arrofi, Abdulhakim., and Nurul Hasfi. “Memahami Pengalaman Komunikasi Orang Tua–Anak Ketika Menyaksikan Tayangan Anak-Anak Di Media Sosial Tik Tok.” Interaksi Online 7, no. 3 (2019): 1–6. Azzahrani, Mardhiyah. “Strategi Komunikasi Pemasaran Kementerian Pariwisata Indonesia Dalam Pesona Indonesia Melalui Youtube.” Jurnal Manajemen Komunikasi 2, no. 2 (2019): 144. https://doi.org/10.24198/jmk.v2i2.12925. Batubara, Azmiani, and Rahmat Hidayat. “Pengaruh Penetapan Harga Dan Promosi Terhadap Tingkat Penjualan Tiket Pada PSA Mihin Lanka Airlines.” Ilman 4, no. 1 (2016): 14. Bulele, Yohana Noni, and Tony Wibowo. “Analisis Fenomena Sosial Media Dan Kaum Milenial: Studi Kasus Tiktok.” Conference on Business, Social Science and Innovation Technology Vol 1, no. No 1 (2020): 565–72. http://journal.uib.ac.id/index.php/cbssit. Haryanto, Handrix Chris, and Tia Rahmania. “Bagaimanakah Persepsi Keterpercayaan Masyarakat Terhadap Elit Politik?” Jurnal Psikologi 42, no. 3 (2015): 243. https://doi.org/10.22146/jpsi.9913. Masruroh, Izzah, and Muhammad Farid. “Pengaruh Pengelolaan Ekonomi Produktif Dalam Mengentaskan Kemiskinan Di Kota Lumajang Studi Pada Badan Amil Zakat Nasional (BAZNAS) Kabupaten Lumajang.” Iqtishoduna: Jurnal Ekonomi Islam Vol.8, no. No.1 (2019): 209–29. http://ejournal.iaisyarifuddin.ac.id/index.php/iqtishoduna/article/view/348. Mohammad Suryawinata, Mohammad Suryawinata. Buku Ajar Mata Kuliah Pengembangan Aplikasi Berbasis Web. Buku Ajar Mata Kuliah Pengembangan Aplikasi Berbasis Web, 2019. https://doi.org/10.21070/2019/978-602-5914-81-2. Ningsih, S. “Strategi Membangun Customer Trust Pada Online Shop Dikalangan Mahasiswa Milenial.” Dinamis: Journal of Islamic Management and … 3, no. 1 (2020): 1–9. http://ejournal.iainpalopo.ac.id/index.php/dinamis/article/view/1576. “Profil LAZNAS Yatim Mandiri,” n.d. https://yatimmandiri.org/about/profil diakses pada tgl 19 desember 2022 pukul 19:09. Purnomo, M. Hadi. “Manajemen Pendidikan Pondok Pesantren,” 2017. Rachmawaty, Asye. “Strategi Marketing Menggunakan Instagram.” ATRABIS: Jurnal Administrasi Bisnis (e-Journal) 7, no. 1 (2021): 39–51. https://doi.org/10.38204/atrabis.v7i1.565. Saragih, Saut Pintubipar, and Mesri Silalahi. “Mengembangkan Usaha Melalui Website Dan Digital Marketing Pada Usaha Teralis Di Kota Batam.” Puan Indonesia 3, no. 2 (2022): 203–12. https://doi.org/10.37296/jpi.v3i2.86. Sumarwan, Ujang. “Model Keputusan Konsumen.” Perilaku Konsumen 5 (2014): 1–41. Wati, Andy Prasetyo, Jefry Aulia Martha, and Aniek Indrawati. “Peningkatan Keterampilan Pemasaran Melalui Pelatihan Whatsapp Business Pada UMKM.” Dedication : Jurnal Pengabdian Masyarakat 4, no. 2 (2020): 137–48. https://doi.org/10.31537/dedication.v4i2.362. Zein, Afrizal, Emi Sita Eriana, Salman Farizy, and Ghema Nusa Persada. “Pembuatan Website CMS (Content Management System) Pada SMK Muhammadiyah Parung Bogor.” Jurnal Ilmu Komputer IV, no. 1 (2021): 70–75. Zulfikri, Zulfikri. “Digital Marketing Communication Dalam Penghimpunan Zakat Di Indonesia.” Jurnal I-Philanthropy: A Research Journal On Management Of Zakat and Waqf 2, no. 1 (2022): 1–8. https://doi.org/10.19109/iphi.v2i1.12927.